Podatki i ich wpływ na konkurencyjność gospodarstw rolnych - Dziemianowicz, Ryta Iwona (Taxes and Their Influence on Competitiveness of Farms, 2006)
The taxation system of agriculture can determine the competitiveness of farms in an essential way. A proper tax construction not only enables to accomplish fiscal aims, it is also able to support the development of farms. The point of this article is to present a hypothetical influence of selected property and income tax constructions on the competitiveness of farms, especially on effectiveness of farming and utilization of the land, on increase or decrease of production and on reproduction of real property. The nature of the present discussion is theoretical and it only refers to selected issues due to the limited size of the article.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 216-221